2021
DOI: 10.1021/acsaelm.1c00330
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Subcycling Behavior of Si-Doped HfO2 Ferroelectric Thin Films

Abstract: The involvement of unwanted subcycling behavior in endurance cycling of HfO2-based ferroelectric thin films is detrimental to the reliability performance of nonvolatile memory devices. Subcycling is also critical for emerging neuromorphic applications as well as multilevel memory cells, which are deliberately operated in subloops of the polarization hysteresis. There is a substantial mismatch between the proven application potential and the lack of basic studies on subcycling behavior. In this work, the temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…However, theoretical calculations also found that the dopant alone is not sufficient to lower the total energy of polar HfO 2 phase to being the lowest among all polar and non-polar polymorphs. Overall, previous experimental and first-principles calculations indicated that the formation of ferroelectric orthorhombic HfO 2 phase in various elemental doped HfO 2 thin films is not only controlled by the intrinsic relatively phase stability of various polar and non-polar HfO 2 polymorphs, but also is related to many other factors, such as surface tension [38,58,59], mechanical stresses [34][35][36], the external electric field [60][61][62], and even the electric polarization history [12,[63][64][65].…”
Section: Introductionmentioning
confidence: 75%
“…However, theoretical calculations also found that the dopant alone is not sufficient to lower the total energy of polar HfO 2 phase to being the lowest among all polar and non-polar polymorphs. Overall, previous experimental and first-principles calculations indicated that the formation of ferroelectric orthorhombic HfO 2 phase in various elemental doped HfO 2 thin films is not only controlled by the intrinsic relatively phase stability of various polar and non-polar HfO 2 polymorphs, but also is related to many other factors, such as surface tension [38,58,59], mechanical stresses [34][35][36], the external electric field [60][61][62], and even the electric polarization history [12,[63][64][65].…”
Section: Introductionmentioning
confidence: 75%
“…As shown in Figure 1g, a single large peak of the switching density corresponding to the hysteresis loop in Figure S5, Supporting Information, suggests a lack of atomic defects, such as oxygen vacancy‐induced internal fields in the ferroelectric material. [ 38–40 ] By adopting coordinate transformation, the switching density can be plotted against the coercive field and the bias field, closely related to the conventional hysteresis (Figure S6, Supporting Information). [ 37 ] Figure 1h shows the multilevel polarization states through the positive region of the polarization hysteresis.…”
Section: Resultsmentioning
confidence: 99%
“…The FORC diagrams provide valuable insights into the complex domain switching properties and the internal bias field in ferroelectrics. [37][38][39][40] The measurement starts from the positive saturated field (E s ) and sweeps between the reversal field (E r ) until the negative saturated field is reached as shown in Figure S5, Supporting Information. With the applied field (E r ≤ E ext ≤ E s ), Figure 1f shows the FORC obtained through the integration of corresponding switching current density (Figure S5, Supporting Information).…”
Section: Ferroelectric Switching Propertiesmentioning
confidence: 99%
“…The difference becomes larger at the woken-up state (~10 3 cycles) because the charge mobilities are higher in elevated temperatures, leading to stronger wake-up effect. On the other hand, the local field generated by the defect migration to non-switchable regions during the fatigue process is also stronger at elevated temperatures [13]. The stronger imprint effect after 10 5 cycles can be observed in 400 K as the P-V loop and the switching current peak are shifted to the positive sides in Fig.…”
Section: Wake-up/fatigue Effects From 4 K To 400 Kmentioning
confidence: 92%